The mediation role of sleep on the relationship between drinks behavior and female androgenetic alopecia - Liu, Shiqi; Gu, Hao; Ji, Ruxin; Shi, Wei; Liu, Fangfen; Xie, Hongfu; Li, Ji; Liu, Yicong; Tang, Yan (PeerJ, 2024)
Objectives To investigate the relationship between drinks behavior and female androgenetic alopecia (AGA) and to clarify the mediating effect of sleep behavior on such relationship. Methods A total of 308 female AGA patients and 305 female normal controls were recruited from the hospital, and questionnaires including drinks behavior and sleep behavior were inquired among them. Blood sugar and blood lipids were detected. Then, the mediating effect of sleep behavior on the relationship between drinks behavior and AGA was analyzed. Results Female AGA patients presented a higher frequency of intake of sweetened tea drinks. It was found that occasional intake (1–2 times per week; ORadj = 2.130, 95% CI [1.495–3.033]) and frequent intake (3–6 time per week; ORadj = 2.054, 95% CI [1.015–4.157]) of sweetened tea drinks were associated with AGA. The daily sugar intake from soft drinks increased the risk of AGA (ORadj = 1.025, 95% CI [1.003–1.048]), and hyperglycemia was positively associated with alopecia (ORadj = 1.897, 95% CI [1.225–2.936]). In addition, bedtime after 12 pm significantly increased the risk of developing alopecia (ORadj = 2.609, 95% CI [1.020–6.676]). Interestingly, bedtime, instead of daily sugar intake from soft drinks, could mediate the relationship between sweetened tea drinks intake and alopecia. Conclusions Sweetened tea drinks consumption increases the risk of female AGA, which is mediated by bedtime.
Keywords: Female androgenetic alopecia; Soft drink intake; Sleep behavior; Metabolic indicators